Designing a framework for establishing mobile payments in Iran - Safaee, Maryam; Jafari, Seyed Mohammad Bagher; Kordnaeij, Asadollah; Soltani, Morteza (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to design a framework for establishing mobile payment in Iran. This study was a qualitative research of data foundation theory whose method is exploratory. In this study, experts active in the first mobile organization in the city of Tehran, as a statistical population were conducted by snowball method and theoretically saturated. This saturation is achieved in the fifteenth interview. However, to ensure the expressed saturation, four more interviews were conducted and the number of sample members reached 19 of these people. In the present study, in order to determine the validity of the measurement instrument, the expert judgment approach on face and content validity has been used. The decision was made based on the opinions of seven academic experts. On the other hand, to evaluate the reliability of the interview protocol, the percentage agreement method between the two coders was used. According to this study, the reliability coefficient for the interview protocol in this study is equal to 74.12%. This amount is a desirable amount from the researchers’ point of view. In the final stage, the factors extracted from the study opinions, experts active in the first mobile organization in the city of Tehran, nine factors and 169 components were extracted. According to the research findings, due to the new mechanism, mobile payment helps to create jobs in various fields and economic growth of the country, and its lack of cash flow also reduces inflation. The framework presented in this research, such as creating non-cash exchanges, reducing the cost of printing money, reducing ecosystem costs, reducing transaction costs in the community, leads to lower transaction costs. The perceived ease of these systems and the wide acceptance they provide for specific receivers. Improving living and social security standards and reducing the risks of cash payments at the community level.